Reactive power planning for maximum load margin improvement using Fast Artificial Immune Support Vector Machine (FAISVM) - Aziz N.F.A.; Abdul Rahman T.K.; Zakaria Z. (Praise Worthy Prize, 2023)
Load margin improvement is an important issue in power system planning and operation. This paper, first, presents a newly voltage stability index called Voltage Stability Condition Indicator (VSCI) to evaluate the voltage stability state of load buses in a system. It also proposes a fast optimization algorithm for reactive power planning problem (RPP) through Fast Artificial Immune Support Vector Machine (FAISVM). FAISVM is a hybrid algorithm that incorporates the application of Artificial Immune System (AIS) and Support Vector Machine (SVM) in solving RPP problems. The newly proposed algorithm can determine the optimal tap settings of tap changing transformers, the value of reactive power injection at the reactive power sources and the injection at the reactive power generator buses. The performances of the techniques proposed were verified using the IEEE 30-bus test system and compared with another newly developed hybrid Evolutionary Support Vector Machine (ESVM). The simulation results have shown that FASIVM outperformed ESVM in terms of maximum load margin improvement and computation time significantly and also reduce active power losses. © 2014 Praise Worthy Prize S.r.l. - All rights reserved.